2014
DOI: 10.1111/jace.13166
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of PbS on Crystallization Behavior of GeS2‐Ga2S3‐Based Chalcogenide Glasses

Abstract: Glass-ceramics of PbS-doped 80GeS 2 Á20Ga 2 S 3 were fabricated by heat treatments of base glasses at T g +30°C for different durations. They exhibited improved mechanical properties such as hardness and resistance to crack propagation, and meanwhile retained their excellent infrared transmission. X-ray diffraction and Raman results indicated that Ga 2 S 3 and GeS 2 crystals were precipitated inside glassy matrix. The crystallization kinetics of base glass was investigated using differential scanning calorimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…This is in agreement with the well‐known fact that, the chemically stoichiometric glass along the tie‐line of the glass‐forming region is the best for the creation of the glass‐ceramics since the growth of the crystals in the glass is much faster. In contrast, S‐rich or S‐poor glasses are much insert against crystallization via thermal annealing of the glasses at a temperature that is 20°C higher than glass transition temperature . On the other hand, the appearance of the difference crystals in chemically stoichiometric glass is mainly due to the formation of GaS 4 tetrahedron rather than Ga 2 S 3 units in the glass, resulting in sulfur deficiency in Ge 30 Ga 4 S 66 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with the well‐known fact that, the chemically stoichiometric glass along the tie‐line of the glass‐forming region is the best for the creation of the glass‐ceramics since the growth of the crystals in the glass is much faster. In contrast, S‐rich or S‐poor glasses are much insert against crystallization via thermal annealing of the glasses at a temperature that is 20°C higher than glass transition temperature . On the other hand, the appearance of the difference crystals in chemically stoichiometric glass is mainly due to the formation of GaS 4 tetrahedron rather than Ga 2 S 3 units in the glass, resulting in sulfur deficiency in Ge 30 Ga 4 S 66 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the different crystals can be formed in the surface and interior of the chalcogenide glass‐ceramics in the previous investigations . In order to examine whether the distribution of these crystals is homogeneous, we polished the annealed Ge 27 Ga 4 S 69 chalcogenide glass‐ceramics with different thickness and measured Raman spectra at several different positions as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As temperature increases, the growth process is predominantly over the surface and two dimensionally it resembles an attachment of discs. The surface morphology of glasses is also studied, using SEM for GeS 2 ‐Ga 2 S 3 glass ceramics . Different types of crystallinity are obtained due to phase segregation in the glass matrix .…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that the Al 2 O 3 ‐YAG amorphous coating possesses high thermal stability due to its large T c and E c . According to the characteristic temperatures obtained from the as‐received DSC data, the width of the supercooled liquid region Δ T 1 = T c1 − T g was widely accepted to be a representative criterion conducting the nucleation resistance, since the larger value of Δ T 1 corresponds to the greater delay in nucleation (namely, larger heat energy needed for nucleation) . The Δ T 1 of the sample at various heating rates were presented in Table .…”
Section: Resultsmentioning
confidence: 99%